Improved documentation following the implementation of a trauma registry: A means of sustainability for trauma registries in low- and middle-income countries - Grant, Chantalle L; Tumuhimbise, Christine; Ninsiima, Consolet; Robinson, Tessa; Eurich, Dean; Bigam, David; Situma, Martin; Saleh, Abdullah (Injury, 2021)
Introduction: Trauma registries in low- and middle-income countries (LMICs) are critical for improv- ing trauma care; however, while some registries have been established in low-income settings, few are sustained due to a lack of sustainable funding. In many LMIC institutions, funding is dependent on doc- umentation of trauma patients, but patient records may be of poor quality, missing, or incomplete. The development of a trauma registry and electronic patient registration system could be used to improve documentation of trauma patients in a low-income setting and lead to increased funding for trauma care. Methods: A retrospective chart review of trauma patients at Mbarara Regional Referral Hospital in Uganda was performed, documenting the monthly admissions from January 2015-July 2016 prior to the establish- ment of a trauma registry. A trauma registry and electronic patient registration system were established in 2017, and monthly admissions from February 2017-December 2019 were documented. A negative bi- nomial regression analysis was performed comparing the incident rate of admission pre-implementation of the registry compared to post-implementation, adjusting for month and year. Completeness of trauma patient records was also assessed. Results: Prior to the implementation of the trauma registry and patient registration system (2015-2016), there was a mean of 5.2 (SD 4.4) trauma records per month identified. Following the implementation of the trauma registry, a mean of 103.4 trauma records per month were documented (SD 32.0) for an increased incident rate ratio of 20.9 (95% CI 15.7-27.6, p < 0.001). There was also a significant increase in percentage of documents completed (OR 49.1, CI 12.4-193.7, p < 0.001). Discussion: Following the implementation of a trauma registry and electronic patient registration system at this low-income country hospital, an increase of 20.9 times completed trauma patient documentation was identified, and completion of the records improved. This more accurate documentation could be used to apply for increased government funding for trauma patients and sustain the trauma registry in the long term and could represent a means of long-term sustainability for other trauma registries in LMICs.
Keywords: Trauma registry; Electronic patient registration; Developing countries; Low- and middle-income countries (LMICs); Uganda; Sustainability